Efficacy of Transversus Abdominal Plane (TAP) block vs. Diclofenac Suppository for Management of Post-Operative Pain in Patients Undergoing Laparoscopic Cholecystectomy - Chauhdry , Mahnoor; Lateef , Muhammad; Tariq , Hassan; Iftikhar , Hira; Amjad, Fatima; Masood, Khizar; Bali, Jabbar Hussain; Yousaf, Shamas (Indus Journal of Bioscience Research, 2025)
Background: Effective post-operative pain management enhances recovery and patient comfort following laparoscopic cholecystectomy. Objective: To evaluate and compare the analgesic efficacy of TAP block versus diclofenac suppository in patients undergoing elective laparoscopic cholecystectomy. Methods: This randomized controlled trial was conducted at the Department of General Surgery, Allama Iqbal Memorial Teaching Hospital, Sialkot. A total of 60 patients scheduled for elective laparoscopic cholecystectomy were randomly allocated into two groups: Group A received bilateral TAP block using the landmark technique, and Group B received a 200 mg diclofenac suppository. All patients received 20 mg/kg intravenous paracetamol. Pain was assessed using the Numeric Rating Scale (NRS) at 2 hours post-operatively. Results: The mean pain score at 2 hours was significantly lower in the TAP block group (2.4 ± 0.9) compared to the diclofenac group (3.8 ± 0.8) (p < 0.001). Rescue analgesia was required in 20% of patients in the TAP block group versus 60% in the diclofenac group (p = 0.003). No complications were reported in either group. Conclusion: The study concludes that the transversus abdominis plane (TAP) block is more effective than diclofenac rectal suppository in managing early post-operative pain after elective laparoscopic cholecystectomy. Patients receiving the TAP block reported significantly lower pain scores and needed less rescue analgesia within the first two hours post-surgery. Additionally, the TAP block showed a favorable safety profile, making it a reliable option in multimodal analgesia, particularly in settings where reducing systemic analgesic use is preferred for better patient outcomes.